A scaled boundary finite element approach for sloshing analysis of liquid storage tanks. (July 2015) - Lin, Gao; Liu, Jun; Li, Jianbo; Hu, Zhiqiang
Abstract: The scaled boundary finite element method (SBFEM) is a promising alternative for sloshing analysis of liquid storage tanks. For linear sloshing problems associated with liquid storage tanks, in most cases, like the upright tanks of arbitrary uniform cross section, the horizontal tanks of arbitrary uniform cross-section and the axisymmetric tanks of arbitrary meridian shape, by employing SBFEM the sloshing analysis can be greatly simplified. Only one dimensional discretization is needed, thus the computational effort is reduced to a great extent, whereas high accuracy of the results is ensured. Numerical examples validate the efficiency and accuracy of the proposed approach.